TRANSLATION METHODS AND STRATEGIES IN THE CONTEXT OF SCIENCE FICTION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Science fiction literature presents unique challenges for translators due to its imaginative nature, technical vocabulary, and invented terminology. The purpose of this article is to analyze the main translation methods and strategies used in translating science fiction texts. Special attention is given to lexical, stylistic, and cultural problems that occur when translating fictional technologies, alien concepts, and futuristic societies. The study discusses commonly used translation methods such as borrowing, calque, adaptation, descriptive translation, and modulation. The article also provides examples from well-known dystopian and futuristic works to demonstrate practical translation decisions. The findings show that successful translation of science fiction requires linguistic competence, creativity, and cultural awareness.